NINJ2 deficiency inhibits preadipocyte differentiation and promotes insulin resistance through regulating insulin signaling. Issue 1 (11th December 2022) - Peng, Huixin; Yu, Yubing; Wang, Pengyun; Yao, Yufeng; Wu, Xinna; Zheng, Qian; Wang, Jing; Tian, Beijia; Wang, Yifan; Ke, Tie; Liu, Mugen; Tu, Xin; et al.
Abstract: Objective: Genetic variants in ninjurin‐2 ( NINJ2 ; nerve injury‐induced protein 2) confer risk of ischemic strokes and coronary artery disease as well as endothelial activation and inflammation. However, little is known about NINJ2 's in vivo functions and underlying mechanisms. Methods: The phenotypes of NINJ2 knockout mice were analyzed, and mechanisms of NINJ2 that regulate body weight, insulin resistance, and glucose homeostasis and lipogenesis were investigated in vivo and in vitro . Results: This study found that mice lacking NINJ2 showed impaired adipogenesis, increased insulin resistance, and abnormal glucose homeostasis, all of which are risk factors for strokes and coronary artery disease. Mechanistically, NINJ2 directly interacts with insulin receptor/insulin‐like growth factor 1 receptor (INSR/IGF1R), and NINJ2 knockdown can block insulin‐induced mitotic clonal expansion during preadipocyte differentiation by inhibiting protein kinase B/extracellular signal‐regulated kinase (AKT/ERK) signaling and by decreasing the expression of key adipocyte transcriptional regulators CCAAT/enhancer‐binding protein β (C/EBP‐β), C/EBP‐α, and peroxisome proliferator‐activated receptor γ (PPAR‐γ). Furthermore, the interaction between NINJ2 and INSR/IGF1R is needed for maintaining insulin sensitivity in adipocytes and muscle via AKT and glucose transporter type 4. Notably, adenovirus‐mediated NINJ2 overexpression can ameliorate diet‐induced insulin resistance in mice. Conclusions: In conclusion, these findings reveal NINJ2 as an important new facilitator of insulin receptors, and the authors propose a unique regulatory mechanism between insulin signaling, adipogenesis, and insulin resistance.